The Influence Of Competency and Dimension Of Uncertainty Avoidance Culture On Restorative Justice Decision Making By Investigators Of The Criminal Research Unit Of Tanjung Pinang Police - Gayuh Pambudhi Utomo; Saut Panggabean Sinaga; Novi Indah Earlyanti; Surya Dharma (International Journal of Economics and Management Research, 2025)
This study aims to analyze the influence of competency and the cultural dimension of uncertainty avoidance on the decision-making process of restorative justice by investigators at the Criminal Investigation Unit of Tanjung Pinang Police . The primary focus is to evaluate the extent to which investigator competency and cultural factors affect the implementation of restorative justice in handling criminal cases. This research employs a quantitative approach with a survey method, using questionnaires distributed to investigators at Tanjung Pinang Police . Data analysis was conducted using multiple regression tests to measure the relationship between independent variables (competency and uncertainty avoidance) and the dependent variable (restorative justice decision-making). The findings reveal that investigator competency has a significant influence on restorative justice decision-making, with a correlation coefficient of 0.851 and a significance value of 0.000 (p < 0.01). Conversely, the cultural dimension of uncertainty avoidance does not have a significant impact, with a correlation value of -0.109 and a significance of 0.496 (p > 0.05). Simultaneously, both variables contribute to restorative justice decision-making, with an R² value of 0.75. This study concludes that investigator competency is the primary factor in implementing restorative justice. Therefore, improving investigators' skills in legal analysis, communication, and mediation is the main recommendation for strengthening the implementation of restorative justice policies at Polresta Tanjung Pinang.